2005
DOI: 10.1007/s00216-005-3358-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of subnanomolar concentrations of cobalt by adsorptive stripping voltammetry at a bismuth film electrode

Abstract: Procedures for trace cobalt determinations by adsorptive stripping voltammetry at in situ and ex situ plated bismuth film electrodes are presented. These exploit the enhancement of the cobalt peak obtained by using the Co(II)-dimethylglyoxime-cetyltrimethylammonium bromide-piperazine-N,N'-bis(2-ethanesulfonic acid) system. The calibration graph for an accumulation time of 120 s was linear from 2 x 10(-10) to 2 x 10(-8) mol L(-1). The relative standard deviation from five determinations of cobalt at a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…This value is comparable to the one obtained with bulk gold substrate and lower with respect to other electroanalytical methods reported in the literature [29][30][31][32][33][34]. It is well known that DMG complexes other metal cations, such as Co(II) [37,40]; for this reason, cobalt is usually considered an interference in the determination of nickel. In order to verify the possible interference of Co(II), the above described analytical procedure was applied for analyzing Ni(II) in the presence of Co(II).…”
Section: M(ii)-dmg2 (Ads) + Ne −  M(ii)-dmg2 N− (2)supporting
confidence: 67%
See 1 more Smart Citation
“…This value is comparable to the one obtained with bulk gold substrate and lower with respect to other electroanalytical methods reported in the literature [29][30][31][32][33][34]. It is well known that DMG complexes other metal cations, such as Co(II) [37,40]; for this reason, cobalt is usually considered an interference in the determination of nickel. In order to verify the possible interference of Co(II), the above described analytical procedure was applied for analyzing Ni(II) in the presence of Co(II).…”
Section: M(ii)-dmg2 (Ads) + Ne −  M(ii)-dmg2 N− (2)supporting
confidence: 67%
“…Briefly, the PPCE was dipped into a 0.1-mol•L −1 ammonium buffer solution containing 10 mg•L −1 Bi(III) in the form of its complex with tartrate and 1 × 10 −5 mol•L −1 dimethylglyoxime (DMG) as the complexing agent. Tartrate was selected in order to avoid the precipitation of bismuth at the pH value necessary for Ni(II) and Co(II) determination [37].…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Tartrate was selected in order to avoid the precipitation of bismuth at the pH value necessary for Ni(II) and Co(II) determination [32]. A twostep accumulation protocol, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, M. Korolczuk et al [31,32], and Sopha et al [33] proposed the use of in situ prepared BiFE and antimony film electrode (SbFE) for measuring solely nickel ions. The only example of simultaneous determination of nickel and cobalt was reported by Korolczuk et al using an in situ prepared lead film electrode (PbFE) [34], but lead is also a toxic element.…”
Section: Introductionmentioning
confidence: 99%
“…7 These electrodes have been applied to determination of many heavy metals such as cadmium, 8 lead, 8 tin, 9 nickel 3,4 and cobalt. 3,4,10,11 Carbon nanotubes (CNT) have attracted much attention in electroanalysis due to the unique mechanical, electronic, geometrical and chemical properties. [12][13][14] In recently years, it has been found that combining metal particles, such as platinum, 15 nickel, 16 copper 17 and palladium, 18 with CNT-modified electrodes can provide a promising way for fabrication of novel electrodes with largely improved performances.…”
Section: Introductionmentioning
confidence: 99%